2008
DOI: 10.4161/cc.7.19.6777
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Arl2 is associated with p53 localization and chemosensitivity in a breast cancer cell line

Abstract: In mammalian cells, ADP ribosylation factor like 2 (Arl2) has been shown to form a complex with tubulin binding cofactor D (TBC-D) and the tumor suppressor protein phosphatase 2A (PP2A). We have previously shown that alterations in Arl2 protein content were associated with corresponding modifications of the tumor suppressor PP2Ac protein content in breast cancer cells. Here, we show that modified Arl2 expression level influences sensitivity to various anticancer compounds such as taxol, navelbine, gemcitabine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
2
33
1
1
Order By: Relevance
“…Our data is consistent with the observations that non-functional p53 affects the sensitivity of cancer cells to GEM [43] and that restoration of p53 function by various approaches in tumors allows activation of molecular pathways that improve the response to GEM [44,45]. Accordingly, some studies demonstrated that exposure to GEM enhances the transcriptional activity of p53 and that GEM-induced apoptosis in cancer cells is mediated by a p53-dependent transcriptional activation of cell death-related genes [46,47]. Here, we showed that the combined treatment of PDAC cells with GEM and p53-reactivating molecules (CP-31398 and RITA) synergistically inhibited cell proliferation in both wt and mp53 tumor cells but not in p53-null cancer cells ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is consistent with the observations that non-functional p53 affects the sensitivity of cancer cells to GEM [43] and that restoration of p53 function by various approaches in tumors allows activation of molecular pathways that improve the response to GEM [44,45]. Accordingly, some studies demonstrated that exposure to GEM enhances the transcriptional activity of p53 and that GEM-induced apoptosis in cancer cells is mediated by a p53-dependent transcriptional activation of cell death-related genes [46,47]. Here, we showed that the combined treatment of PDAC cells with GEM and p53-reactivating molecules (CP-31398 and RITA) synergistically inhibited cell proliferation in both wt and mp53 tumor cells but not in p53-null cancer cells ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…When our latest observations are combined with earlier studies, we conclude that ARL2 is an important component of several cellular processes, including (i) regulation of ATP levels in mitochondria, likely in the matrix, (ii) regulation of mitochondrial fission and motility, (iii) at centrosomes, in concert with cofactor D, to regulate the growth of microtubules and mitotic spindles [10], [11], [22], [47], [76], (iv) in the nucleus to regulate STAT3 and perhaps other transcriptional responses [12], and in the cytosol to (v) regulate the folding of tubulin heterodimers [2], [3], and (vi) the shuttling and release of farnesylated proteins [24]. With the dissection of these different functions of ARL2 and the growing list of reagents allowing their clear resolution we are poised to understand the mechanisms of these actions at the molecular level, though some of them are expected to be challenging to document due to the limited understanding of the process itself (e.g., crista junction regulation).…”
Section: Discussionsupporting
confidence: 58%
“…In addition to changes in mitochondrial morphology, we also noted that cells deficient in ARL2 activity, either resulting from depletion by siRNA or expression of ARL2[T30N], appear to be smaller than controls. This size difference was not quantified or explored further in the current study but was reported earlier in related studies [10], [11], [22].…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Death observed in tumor cells but not in normal fibroblasts indicates that destabilization induced by MESQ was completely reversible or innocuous in cells with genomic stability and normal functions, including regulation and repair mechanisms, as already shown in various studies (Ali, 2007;Béghin et al, 2008;Hartwig et al, 2009). On the contrary, cells of the MCF7 tumor line, characterized by genomic instability, aneuploid chromosomes (hypertriploid-hypotetraploid), and aberrant cell function, were completely destabilized by MESQ, as shown by the large population of apoptotic cells after 3 h of exposure (Figs.…”
Section: Discussionmentioning
confidence: 72%